Uporabniška izkušnja v COBISS+ - Švab, Katarina (Organizacija znanja, 2021)
User experience is becoming an increasingly important aspect of the quality of services, products and even bibliographic information systems. Due to the lack of comprehensive research into user experience in bibliographic information systems, we developed a questionnaire, covering all key dimensions and aspects of user experience and taking into account the specificities of bibliographic information systems. The article presents findings about the user experience with COBISS+ and the tested questionnaire. The survey was conducted in the form of an online survey between 15 and 24 June 2020, in which 418 users of the COBISS+ library catalogue participated. The results showed that, on average, the experience of the participating users was positive, they felt satisfied and relaxed when using the system and mainly saw COBISS+ as useful, efficient, easy to learn, useful and practical. There were also some differences in experience depending on the purpose of use, previous experience with the system and the gender of the respondent. The consistency of the results obtained for different types of the same question and also for all three sets of questions indicates that the tested questionnaire is useful and appropriate and allows certain conclusions to be drawn despite the limitations of the study. The main limitation of the study is the sample obtained, where the majority of respondents are frequent and older COBISS+ users. The results provide an insight into the user experience in COBISS+ and present a starting point for further research. They also enable the evaluation and further improvements of the questionnaire.
Keywords: bibliografski informacijski sistemi; bibliographic information systems; COBISS+; evaluation; uporabniška izkušnja; user experience; UX; vrednotenje